Persistent Neutrophil Dysfunction and Suppression of Acute Lung Injury in Mice following Cecal Ligation and Puncture Sepsis - Grailer, Jamison J. (S. Karger AG, 2014)
Sepsis, both in humans and in rodents, is associated with persistent immunosuppression accompanied by defects in innate immunity during the acute phase of sepsis. Mice were rendered septic by cecal ligation and puncture (CLP) followed by the induction of acute lung injury, employing distal airway deposition of IgG immune complexes, in order to quantitatively evaluate innate immune responses following the induction of sepsis. Suppression of innate immune responses in the lung occurred as early as 12 h after CLP and up to 21 days thereafter. The mechanism of innate immune defects included a reduced leak of albumin into the lungs together with reduced levels of tumor necrosis factor in bronchoalveolar lavage fluids and increased levels of interleukin-10 that were persistent. Bone marrow-derived neutrophils (polymorphonuclear neutrophils; PMNs) from CLP mice also had reduced levels of the activation marker CD11b and a depressed respiratory burst following stimulation in vitro. These results were not observed in mice with endotoxemia, where the innate inflammatory response was preserved. However, sustained lymphopenia was present in both models, suggesting differential regulation of innate and adaptive immunity in the two sepsis models. These data indicate that CLP induced a prolonged suppression of inflammatory responses both in the lung and systemically, as defined by bone marrow-derived PMN dysfunction.